The Mapping of English for Bussiness Communication Competence of the Students of Vocational Schools in Coastal Areas (Dumai, Bengkalis, Meranti, and Inhil) in Riau Province - Ras, Fakhri; Syarfi, Mohd.; Syafrianti, Maria (Proceedings of the UR International Conference on Educational Sciences, 2018)
This study aims at getting an accurate map of English for Bussiness Communication Competenceof the students of vocational schools in coastal areas of Riau Province in the form of writing ability. The target group of the study are the students of the vocational schools as big as 2476 students. Due to thehomogenous characters of the population, in term of age and academic backgrounds, the sample is taken randomly as big as 25% out of them that is 619 students. The thehnique of collecting data is asking the respondents to write personal letter and curriculum vitae.The collected data are judged by using Brownâs writing description (Brown:2004). The findings are as the following: a). the the average of the respondentsâ writing ability in personal letter is 3.45 out of 4, b). the average of the respondents writing ability in curriculum vitae is 3.24 out of 4. The implication of these findings are that the respondents should be given more exercises, and corrections in using structure and vocabulary items in order to achieve the standard use of two language compenents in making personal letter and curriculum vitae.